Detection of Second Line Drug Resistance among Drug Resistant Mycobacterium Tuberculosis Isolates in Botswana - Tuelo Mogashoa; Pinkie Melamu; Brigitta Derendinger; Serej D. Ley; Elizabeth M. Streicher; Thato Iketleng; Lucy Mupfumi; Margaret Mokomane; Botshelo Kgwaadira; Goabaone Rankgoane-Pono; Thusoyaone T. Tsholofelo; Ishmael Kasvosve; et al. (Pathogens, 2019)
The emergence and transmission of multidrug resistant (MDR) and extensively drug resistant (XDR) Mycobacterium tuberculosis (M.tb) strains is a threat to global tuberculosis (TB) control. The early detection of drug resistance is critical for patient management. The aim of this study was to determine the proportion of isolates with additional second-line resistance among rifampicin and isoniazid resistant and MDR-TB isolates. A total of 66 M.tb isolates received at the National Tuberculosis Reference Laboratory between March 2012 and October 2013 with resistance to isoniazid, rifampicin or both were analyzed in this study. The genotypes of the M.tb isolates were determined by spoligotyping and second-line drug susceptibility testing was done using the Hain Genotype MTBDRsl line probe assay version 2.0. The treatment outcomes were defined according to the Botswana national and World Health Organization (WHO) guidelines. Of the 57 isolates analyzed, 33 (58%) were MDR-TB, 4 (7%) were additionally resistant to flouroquinolones and 3 (5%) were resistant to both fluoroquinolones and second-line injectable drugs. The most common fluoroquinolone resistance-conferring mutation detected was gyrA A90V. All XDR-TB cases remained smear or culture positive throughout the treatment. Our study findings indicate the importance of monitoring drug resistant TB cases to ensure rapid detection of second-line drug resistance.